Relationships between families’ use of Sure Start Children’s Centres, changes in home learning environments, and preschool behavioural disorders - Hall, J; Sammons, P; Smees, R; Sylva, K; Evangelou, M; Goff, J; Smith, T; Smith, G (Taylor and Francis, 2019)
UK Sure Start Children’s Centres (SSCCs) aim to lessen behavioural disorders yet we lack evidence concerning how this is achieved. This study evaluates one possible mechanism: improved home learning environments (HLEs). Data come from a longitudinal study of 2568 families and children recruited at a mean age of 14 months from 117 SSCCs in England in 2012. Behavioural disorders were measured at 38 months via the Strengths and Difficulties Questionnaire. HLEs were measured at 14 and 38 months via parental interview. Families’ use of SSCCs was measured via parental interview at 14, 22, and 38 months. This study suggests that the use of SSCCs is associated with fewer preschool behavioural disorders via intermediate changes to the quality of HLE’s. Implications are discussed for social policies and for early years’ professionals.